Uji Kevalidan Modul Berorientasi Higher Order Thinking Skills (HOTS) pada Materi Biologi Kelas XI Semester Genap untuk Mendukung Kurikulum Merdeka - Dini, Dwi Rahayu; Adnan, Adnan; Ali, Alimuddin (Bioscientist : Jurnal Ilmiah Biologi, 2023)
The Merdeka curriculum directs the learning process according to the needs of students and their learning environment. The need for teaching materials that are in accordance with the Merdeka curriculum encourages successful learning in schools. This encourages the development of modules oriented towards higher order thinking skills that are valid in the biology material class XI even semester through the application of the Merdeka curriculum. This research is a development research (Research and Development). Data collection was carried out using an instrument in the form of a HOTS-oriented product validation questionnaire which was assessed by 2 expert validators. The results of validator assessments related to module validity reached an average percentage of 4.40 in the valid category. The results showed that the modules developed had been validated and declared valid to be used as teaching materials in the biology learning process in class XI even semester. The modules developed can be used to support the learning process in schools and independent learning carried out by students alone or in groups and to facilitate students' understanding of biology subjects with HOTS competencies.